107 The Prevalence, Predictors and Outcomes Associated with Anaemia Among Patients that Present with ACS: Insights from the UK MINAP Registry. (3rd June 2016) - Kwok, Chun Shing; Mamas, Mamas A; Kontopantelis, Evangelos; Fryer, Anthony A; Buchan, Iain; Bachmann, Max O; Justin Zaman, M; Myint, Phyo K
Abstract : Background: Data from both registry and post-hoc analysis of randomised controlled trials have suggested that the burden of anaemia among patients admitted with acute coronary syndrome (ACS) is significant. However, current guidelines fail to offer firm recommendations for its concurrent management in the ACS settings. Methods: The Myocardial Ischemia National Audit Project (MINAP) registry collects data on all patients age 18 years or over who are admitted to all 230 NHS hospital trusts in England and Wales with a diagnosis of ACS. We conducted a retrospective cohort study for all ACS patients admitted on the MINAP registry between January 2006 to December 2010 and followed up these participants until August 2011 for mortality. Multiple logistic regression was used to calculate independent predictors of anaemia and the adjusted odds of 30-day and 1-year mortality for anaemic and non-anaemic group. Additional analysis was performed evaluating the odds of mortality with incremental 1 g/dl increase in haemoglobin. Results: A total of 422, 855 participants with ACS were included in the analysis and 27.7% of these participants were anaemic. Anaemic participants were older (OR 1.046, 95% CI 1.045–1.046) and had a greater prevalence of co-morbid conditions (renal disease (OR 3.06, 95% CI 2.96–3.16), peripheral vascular disease (OR 1.43, 95% CI 1.36–1.50), diabetes mellitus (OR 1.79, 95% CI 1.74–1.83) and previous acute myocardial infarction (OR 1.21, 95% CI 1.18–1.24)) and are less likely to receive evidence based therapies shown to improve clinical outcomes. Further analysis suggested that anaemia is independently associated with 30-day (OR 1.28, 95% CI 1.22–1.35) and 1-year mortality (OR 1.31, 95% CI 1.27–1.35). We observed a reverse J-shaped relationship between haemoglobin levels and mortality outcomes. Conclusions: In this largest study to date of anaemia in ACS, we report that approximately one in four patients presenting with ACS are anaemic and these patients are older with more co-morbid conditions and are less likely to receive evidence based therapies. Anaemic patients are also more likely to have adverse outcomes. Whilst the clinical effectiveness of correcting anaemia routinely in ACS has not been widely explored, there is considerable uncertainty in the value of such an approach. Targeted intervention strategies in this patient population should be explored.